The impacts of family treatment drug court on child welfare core outcomes: A meta-analysis - Zhang, Saijun; Huang, Hui; Wu, Qi; Li, Yong; Liu, Meirong (Child abuse & neglect, 2019)
Substance abuse has been prevalent among caregivers involved in child welfare and is a major barrier to their achieving favorable outcomes. Family Treatment Drug Courts (FTDCs) have been viewed as one of the most promising interventions but research has reported mixed effects on child welfare outcomes. No meta-analysis was conducted to synthesize the findings to reach a more generalizable conclusion. The meta-analysis synthesized findings from existing evaluations to examine whether and to what extent FTDC participants achieved better reunification and safety outcomes than non-participants. Among 17 identified studies dated from 2004 to 2018, the pooled sample subjects in the intervention and comparison groups were 3402 and 3683 for the 16 studies on reunification outcomes, and 842 and 632 for the eight studies on child safety outcomes. We first estimated the FTDCs’ pooled effects on child reunification and safety outcomes. Furthermore, we conducted a series of subgroup meta-analysis to compare FTDCs’ effects across study and program characteristics. Subjects participating in FTDCs were substantially more likely to achieve reunification (OR = 1.75, 95% CI = 1.38, 2.22) without increasing the risk of subsequent foster care reentry or maltreatment re-report. Subgroup meta-analysis suggests factors such as research design, FTDC model, observation length, publication type and period may contribute to FTDCs’ disparities on reunification outcomes. The synthesized findings strengthen evidence for the implementation and expansion of FTDCs for serving substance abusing caregivers in the child welfare system.